Impact of wireless networking technology on social interaction in Cairo’s public spaces - Nouran Hatem; Abeer Elshater; Samy Afifi; Abdulmoneim Alfiky (Ain Shams Engineering Journal, 2024)
The rapid advancement of wireless networking technology has fundamentally altered how people interact in public spaces, leading to concerns about its impact on social interactions. This research identifies factors that influence social interaction in public spaces due to the wireless networking technology by analysing responses from 333 participants using Statistical Package for Social Sciences (SPSS), correlation analysis, Friedman’s ANOVA and thematic analysis. Our results indicated that despite the prevalence of wireless networking technology, public spaces remain essential for social interaction. The study categorises public spaces into four types based on its users’ needs: (1) technology-free zones that emphasise physical interaction, (2) tech-enabled public spaces supporting connectivity and work, (3) interest-based public spaces offering specific activities, and (4) interactive public spaces designed with dynamic features to engage users. These findings provide valuable guidance for urban designers to balance technological integration with the need for meaningful social interactions in public spaces.